2017
DOI: 10.1038/srep40543
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Isotope Labeling LC-MS for Monitoring Disease Progression and Treatment in Animal Models: Plasma Metabolomics Study of Osteoarthritis Rat Model

Abstract: We report a chemical isotope labeling (CIL) liquid chromatography mass spectrometry (LC-MS) method generally applicable for tracking metabolomic changes from samples collected in an animal model for studying disease development and treatment. A rat model of surgically induced osteoarthritis (OA) was used as an example to illustrate the workflow and technical performance. Experimental duplicate analyses of 234 plasma samples were carried out using dansylation labeling LC-MS targeting the amine/phenol submetabol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 69 publications
2
27
0
Order By: Relevance
“…The rat model used for metabolomics study of rheumatoid arthritis (RA) has been described previously. 18 The samples collected from the rats consisted of 7 groups, including a group of normal controls (n = 96), RA, and other treated rats. In total, there were 468 samples, which were processed and analyzed in three batches.…”
Section: Plasma Samples and Sample Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…The rat model used for metabolomics study of rheumatoid arthritis (RA) has been described previously. 18 The samples collected from the rats consisted of 7 groups, including a group of normal controls (n = 96), RA, and other treated rats. In total, there were 468 samples, which were processed and analyzed in three batches.…”
Section: Plasma Samples and Sample Processingmentioning
confidence: 99%
“…Each sample was labeled using 12 C-dansylation after protein precipitation, and the resultant labeled sample was analyzed by LC-UV to measure the total concentration of labeled metabolites for sample amount normalization. 18,19 Based on the total concentration, an appropriate volume of an individual unlabeled sample was taken to mix with an equal mole amount of other unlabeled samples to generate a pooled sample, which was then labeled by 13 C-dansylation. An equal mole amount of the 12 C-labeled individual sample and the 13 Clabeled pooled sample was mixed for LC-TOF-MS analysis.…”
Section: Plasma Samples and Sample Processingmentioning
confidence: 99%
“…Well-controlled animal models offer inherent phenotypes for specific diseases or abnormal conditions. Therefore, biological samples from animal models are often used in metabolomics studies [86,87,88]. However, only a few metabolomics studies have been conducted using animal hair.…”
Section: Use In Animal Studiesmentioning
confidence: 99%
“…In rat models of OA, changes to amino acid metabolism are also observed in urine [41]. Again in rats, a longitudinal metabolomic analysis of plasma showed that there are significant and time-dependent changes in products of lysine metabolism after surgical induction of OA [42]. This further suggests that amino acid metabolism may contribute to OA pathology or that select amino acid levels could be used as biomarkers of OA incidence and progression.…”
Section: The Local and Systemic Metabolomes Of Osteoarthritismentioning
confidence: 99%